Utilizing an Oxyhydrogen Reactor to Produce Hydrogen Gas as a New Source of Energy from Textile Effluent - Rusdianasari; Isdaryanto Iskandar; Prita Dewi Basuki (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
Textile wastewater can disrupt the environmental equilibrium. One type of textile waste processing is the production of hydrogen gas as a new and sustainable energy source. The water electrolysis method may be used to convert textile waste into hydrogen gas. In this study, hydrogen gas was produced from textile waste in two stages: electroplating waste treatment with an electrocoagulator and then processing textile waste into hydrogen gas using an oxyhydrogen reactor. Various catalysts, including NaOH, KOH, NaCl, and NaHCO3, were used in the process of converting textile waste into hydrogen gas, with a concentration of 0.5 M and an electrolysis period of 5 minutes. The addition of a catalyst is intended to identify the optimal concentration in the conversion of textile waste to hydrogen gas. The optimal KOH catalyst concentration for obtaining hydrogen gas was determined through study and analysis.